2022
DOI: 10.3390/ijerph191912592
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Flood Risks of Rainfall and Storm Tides Affected by the Parameter Estimation Coupling Bivariate Statistics and Hydrodynamic Models in the Coastal City

Abstract: : The public health risk caused by urban floods is a global concern. Flood risks are amplified by the interaction of rainfall and storm tides in coastal cities. In this study, we investigate the flood risks of rainfall and storm tides coupling statistical and hydrodynamic models and evaluate the influence of different parameter estimation methods and bivariate return periods (RPs) on flood risks in the coastal city. The statistical model is used to obtain the bivariate design of rainfall and storm tides with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…To establish the input parameters for the proposed alternatives, historical annual peak discharges of the Jamuna River spanning the last 65 years (1956-2021) were scrutinized. Subsequently, three distinct peak discharges were chosen as input data to simulate the selected stretch of the Jamuna River by employing Gumbel's distribution method, [30] as outlined in the following Table 1…”
Section: Options For New Countermeasuresmentioning
confidence: 99%
“…To establish the input parameters for the proposed alternatives, historical annual peak discharges of the Jamuna River spanning the last 65 years (1956-2021) were scrutinized. Subsequently, three distinct peak discharges were chosen as input data to simulate the selected stretch of the Jamuna River by employing Gumbel's distribution method, [30] as outlined in the following Table 1…”
Section: Options For New Countermeasuresmentioning
confidence: 99%
“…Using rainfall data from NASA, we found that southern parts of the SRB were comparatively more susceptible to floods than its northern territories. This is because SRB has semi-arid climatic conditions where the rainfall pattern in lower southern parts is influenced by the summer monsoon, while in upper northern parts, the rainfall pattern is dominated by the winter rainfall, occurring due to the western disturbance of the Mediterranean Sea (Khan et al, 2020;Wang et al, 2020;Hussain et al, 2021;Xu et al, 2022).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%
“…For example, the dependence between observed water levels and precipitation, including impacts of sampling methods and distribution fitting and the resulting flood values, is explored using copulas in [22]. The joint distribution of rainfall and storm surge based on the copula function is investigated in [23]. The effect of internal climate variability on copula-based compound event analysis is studied in a case study in the Netherlands by [24].…”
Section: Introductionmentioning
confidence: 99%